Hypoglossal Neuropathology and Respiratory Activity in Pompe Mice - Lee, Kun-Ze (Frontiers Research Foundation, 2011)
Pompe disease is a lysosomal storage disorder associated with systemic deficiency of acid α-glucosidase (GAA). Respiratory-related problems in Pompe disease include hypoventilation and upper airway dysfunction. Although these problems have generally been attributed to muscular pathology, recent work has highlighted the potential role of central nervous system (CNS) neuropathology in Pompe motor deficiencies. We used a murine model of Pompe disease to test the hypothesis that systemic GAA deficiency is associated with hypoglossal (XII) motoneuron pathology and altered XII motor output during breathing. Brainstem tissue was harvested from adult Gaa(−/−) mice and the periodic acid Schiff method was used to examine neuronal glycogen accumulation. Semi-thin (2 μm) plastic sections showed widespread medullary neuropathology with extensive cytoplasmic glycogen accumulation in XII motoneuron soma. We next recorded efferent XII bursting in anesthetized and ventilated Gaa(−/−) and B6/129 mice both before and after bilateral vagotomy. The coefficient of variation of respiratory cycle duration was greater in Gaa(−/−) compared to B6/129 mice (p < 0.01). Vagotomy caused a robust increase in XII inspiratory burst amplitude in B6/129 mice (239 ± 44% baseline; p < 0.01) but had little impact on burst amplitude in Gaa(−/−) mice (130 ± 23% baseline; p > 0.05). We conclude that CNS GAA deficiency results in substantial glycogen accumulation in XII motoneuron cell bodies and altered XII motor output. Therapeutic strategies targeting the CNS may be required to fully correct respiratory-related deficits in Pompe disease.